Assuring the Proper Analytical Performance of Measurement Procedures for Immunosuppressive Drug Concentrations in Clinical Practice: Recommendations of the International Association of Therapeutic Drug Monitoring and Clinical Toxicology Immunosuppressive Drug Scientific Committee. Issue 2 (April 2016) - Seger, Christoph; Shipkova, Maria; Christians, Uwe; Billaud, Elaine M.; Wang, Ping; Holt, David W.; Brunet, Mercè; Kunicki, Paweł K.; Pawiński, Thomasz; Langman, Loralie J.; Marquet, Pierre; Oellerich, Michael; et al.
Abstract : Abstract: Monitoring immunosuppressive drugs (ISDs) in blood or plasma is still a key therapeutic drug monitoring (TDM) application in clinical settings. Narrow target ranges and severe side effects at drug underexposure or overexposure make accurate and precise measurements a must. This overview prepared by the Immunosuppressive Drugs Scientific Committee of the International Association of Therapeutic Drug Monitoring and Clinical Toxicology is intended to serve as a summary and guidance document describing the current state-of-the-art in the TDM of ISDs.